Lexically-Based Language Teaching: Metaphor In English For Specific Purposes - Siusana Kweldju (Universitas Negeri Malang, 2016)
Metaphor can be a semi-technical vocabulary in ESP. In fact, it is abundant in all branches of science. Being a significant part of human conceptual system, it plays a basic role in the imaginative cognitive mechanism, which is common not only in daily activities but also in scientific inquiry. Although most ESP materials have been developed based on careful research and needs analysis on lexicon, metaphor has been ignored in the teaching of ESP. Lexically-based language teaching, however, underlines the importance of metaphor in ESP.